Diseño de un visor web para la difusión de datos de percepción socio ambientales - Mora Abendaño, Andrés Mateo (2018)
Abstract:The geospatial visualization of the information focused on a research or study is easier to interpret through a web viewer. The visualization by a web viewer is very versatile since it has interactive tools that allow the user to manipulate the information about what they want to investigate. Generally, the viewer is contemplated into a data observatory, adding additional value to the viewer, that makes it a strong social tool which allows data sharing with any user of the web. The observatories could use web viewers to represent it, by an attractive and visual way data and relevant current information on the topic which they are focused. The objective of this work is design a web data viewer for the observatory of socio-environmental perceptions, whose data were collected between the years 2016 - 2017 through surveys applied in 31 cantons of Ecuador.